2017
DOI: 10.1093/rheumatology/kex079
|View full text |Cite
|
Sign up to set email alerts
|

The problem in differentiation between psoriatic-related polyenthesitis and fibromyalgia

Abstract: The recognition of the primacy of enthesitis in animal models of spondyloarthritis and the prevalence of clinically occult enthesopathy in psoriatic subjects and of persistent joint pain in PsA subjects who have ostensibly good reduction of joint swelling under biological therapy has highlighted the potential impact of polyenthesitis in psoriatic disease. In daily practice, the formal demonstration of enthesitis is challenging for the following reasons: the relatively avascular nature of enthesis, often leadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 56 publications
1
43
0
3
Order By: Relevance
“…In routine clinical practice, there has been an increase in the use of US for both diagnosis and monitoring of PsA. In borderline cases with psoriasis and musculoskeletal (MSK) pain, US can be very helpful to differentiate inflammatory synovitis or enthesitis from other common conditions including osteoarthritis (OA) and mechanical joint pain 13,14,15 . Once a diagnosis is established, US can also be used to quantify inflammation in joints and tendons if there is doubt in the clinical examination 13 .…”
Section: Editorialmentioning
confidence: 99%
“…In routine clinical practice, there has been an increase in the use of US for both diagnosis and monitoring of PsA. In borderline cases with psoriasis and musculoskeletal (MSK) pain, US can be very helpful to differentiate inflammatory synovitis or enthesitis from other common conditions including osteoarthritis (OA) and mechanical joint pain 13,14,15 . Once a diagnosis is established, US can also be used to quantify inflammation in joints and tendons if there is doubt in the clinical examination 13 .…”
Section: Editorialmentioning
confidence: 99%
“…В недавнем исследовании A. Marchesoni и соавт. [27] показано, что раннее выявление энтезита существенно меняет прогноз и тактику лечения ПсА.…”
Section: клинические проявления псаunclassified
“…Entheseal regions are well-innervated, but are completely avascular at attachment sites and have a low density of blood vessels in the adjacent ligaments and tendons ( 60 ). On this basis, although pain, tenderness and stiffness are its main clinical manifestations, in most cases enthesitis occurs without visible signs of clinical inflammation and without increased acute phase reactants ( 61 ). Moreover, many entheses are not clinically accessible, located deep inside the human body.…”
Section: Imaging To Differentiate Spa From Fmmentioning
confidence: 99%
“…This may be explained by the presence of subclinical enthesitis, which may be related to other conditions inducing mechanical stress, such as high BMI or physical overuse ( 77 ). Although all the above progress is promising, WB-MRI technique is still under development and, before widespread clinical use, robust research and clarification concerning entheseal abnormalities found also in healthy subjects are needed ( 61 ). Although enthesitis is considered as the primary pathological process underling SpA, it is still difficult to differentiate whether patients have poly-enthesitis, FM or both, because the physical examination may be similar, and other clinical features, for example the response to NSAIDs, need to be taken into consideration.…”
Section: Imaging To Differentiate Spa From Fmmentioning
confidence: 99%